Carbapenem Resistance among Enterobacter Species in a Tertiary Care Hospital in Central India. (10th August 2014) - Khajuria, Atul; Praharaj, Ashok Kumar; Kumar, Mahadevan; Grover, Naveen
Abstract : Objective . To detect genes encoding carbapenem resistance among Enterobacter species in a tertiary care hospital in central India. Methods . Bacterial identification of Enterobacter spp. isolates from various clinical specimens in patients admitted to intensive care units was performed by routine conventional microbial culture and biochemical tests using standard recommended techniques. Antibiotic sensitivity test was performed by standard Kirby Bauer disc diffusion technique. PCR amplification and automated sequencing was carried out. Transfer of resistance genes was determined by conjugation. Results . A total of 70/130 (53.84%) isolates of Enterobacter spp. were found to exhibit reduced susceptibility to imipenem (diameter of zones of inhibition ≤13 mm) by disc diffusion method. Among 70 isolates tested, 48 (68.57%) isolates showed MIC values for imipenem and meropenem ranging from 32 to 64 mg/L as per CLSI breakpoints. All of these 70 isolates were found susceptible to colistin in vitro as per MIC breakpoints (<0.5 mg/L). PCR carried out on these 48 MBL (IP/IPI)E -test positive isolates (12 Enterobacter aerogenes, 31 Enterobacter cloacae, and 05 Enterobacter cloacae complex) was validated by sequencing for beta-lactam resistance genes and result was interpreted accordingly. Conclusion . The study showed MBL production as an important mechanism in carbapenem resistance in Enterobacter spp. and interspecies transfer of these genes through plasmids suggesting early detection by molecular methods.